Removal of heavy metals derived from COD analysis wastewater by electrolysis using graphite electrode - Thi Thanh Diem Ngo; Minh Tien Tran (Vietnam Journal of Science, Technology and Engineering, 2021)
In this study, electrolysis using graphite electrodes was applied to treat wastewater generated from a COD analysis procedure (referred to as COD wastewater). COD wastewater containing high concentrations of H2SO4, Hg2+, and Cr2O72- salts were collected and then treated by electrolysis with graphite electrodes in a labscale experiment. The results showed that the electrolysis process was not affected by the electrode’s distance or area. The most efficient treatment for all three metals was achieved at a current value of 31.58 mA, which corresponds to a current density of 1.974 mA/cm2 under a voltage of 3 V, 8-h electrolysis time, wastewater pH<1, electrode distance of 4 cm, and electrode area of 16 cm2. Under these conditions, the concentrations of heavy metals after treatment were 1170.17 mg/l for Hg, 871.20 mg/l for Ag, and 56.3 mg/l for Cr. The treatment efficiencies were 48.15, 66.94, and 50.76%, for Hg, Ag, and Cr, respectively. While this technology is simple, low cost, and achieves a relatively high efficiency, after treatment the COD wastewater still carried a high concentration of heavy metals that exceeded the permissible standards. Therefore, it is necessary to have a further treatment method in place to completely eliminate the heavy metals remaining in wastewater, as well as to recycle and reuse acidic components from wastewater and to treat them up to environmental standards before discharge. In conclusion, electrolysis with graphite electrodes can be applied in practice to treat other sources of wastewater contaminated by heavy metals with low emissions.